Research of mutual inductance voltage between stators of six-phase induction motor - NIU Lianbo; FU Huikai; AI Yongle (Gong-kuang zidonghua, 2014)
Theoretical calculation and finite element analysis of coefficients of transient self-inductance and mutual inductance between stators and mutual voltage were carried out when trapezoidal wave phase current was input to six-phase induction motor. The calculation and analysis results show that six-phase induction motor whose stator side inputting trapezoidal wave can simulate control mode of DC motor; Torque current has very little impact on induced voltage of each phase of the stator, which verifies reasonableness of ignoring magnetic effect generated by stator torque current and rotor current during modeling and simulation.